Hosts and impacts of elongate hemlock scale (Hemiptera: Diaspididae): A critical review - Venette, Robert C.; Ambourn, Angie; Aukema, Brian H.; Jetton, Robert M.; Petrice, Toby R. (Frontiers in Insect Science, 2024)
Fiorinia externa Ferris, elongate hemlock scale, was inadvertently introduced to North America from Japan. This insect is particularly problematic on hemlock, Tsuga spp., though it has been reported in association with several other conifers. The evidence that other conifers might be hosts, capable of supporting growing populations of the insect, has not been previously reviewed. Our review confirms that F. externa is an oligophagous pest of members of Pinaceae. Although species of Cupressaceae and Taxaceae have been reported as hosts of F. externa, they seem unable to support population growth of this pest. Evidence of the tree-killing potential of the insect, even on suitable hosts, is remarkably scant. The degree of pest risk posed by F. externa with respect to tree mortality in areas beyond the geographic range of hemlock seems modest, but uncertain.